Influence of the interface material layers and semiconductor energetic disorder on the open circuit voltage in polymer solar cells. Issue 10 (21st February 2015) - Zampetti, Andrea; Fallahpour, Amir Hossein; Dianetti, Martina; Salamandra, Luigi; Santoni, Francesco; Gagliardi, Alessio; Auf der Maur, Matthias; Brunetti, Francesca; Reale, Andrea; Brown, Thomas M.; Di Carlo, Aldo
ABSTRACT Material layers at electrode/semiconductor interfaces are fundamental for the photovoltaic properties of polymer solar cells. The relationship between open‐circuit voltage (VOC) and the work function (φ) of these interface layers is still a matter of debate. Simulations, together with experiments on over more than 20 cell architectures based on P3HT:PC60BM, enabled us to analyze the physical dependence of VOC on φ. In particular, when the work function of the contacts is well inside the gap we observe that performance depends strongly on even small variations of φ. On the other hand, when it approaches the energy levels of the semiconducting polymers, device operation becomes the most efficient and less sensitive to variations in φ. Furthermore, by varying the Gaussian density of states (DOS) of the active blend we were able to show that VOC performance depends significantly also on the DOS. Our study based on the simultaneous variation of transport layers represents a promising method to optimize the design and performance of polymer solar cells. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 690–699